2019
DOI: 10.3389/fonc.2019.00808
|View full text |Cite|
|
Sign up to set email alerts
|

Exogenous Let-7a-5p Induces A549 Lung Cancer Cell Death Through BCL2L1-Mediated PI3Kγ Signaling Pathway

Abstract: Elevated expression of let-7a-5p contributes to suppression of lung cancer, in which let-7a-5p, as exosome cargo, can be transported from macrophages to lung cancer cells, yet the role of let-7a-5p remains unclear. Utilizing bioinformatics methods and cellular experiments, this study was designed and conducted to identify let-7a-5p regulatory network in lung cancer. Bioinformatics analysis and Kaplan-Meier survival analysis revealed that let-7a-5p could directly target BCL2L1, and aberrant expression of let-7a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…25 Duan et al found that let-7a-5p restrained the proliferation and metastasis while facilitated the death of lung cancer cells via inversely modulating BCL2L1. 26 Kim et al proved that the level let-7a-5p was reduced in BC tissues and cells, and it repressed the proliferation and metastasis of BC cells through CCR7. 27 Herein, we focused on the role of let-…”
mentioning
confidence: 99%
“…25 Duan et al found that let-7a-5p restrained the proliferation and metastasis while facilitated the death of lung cancer cells via inversely modulating BCL2L1. 26 Kim et al proved that the level let-7a-5p was reduced in BC tissues and cells, and it repressed the proliferation and metastasis of BC cells through CCR7. 27 Herein, we focused on the role of let-…”
mentioning
confidence: 99%
“…As the most critical component of non-small-cell lung cancer, lung adenocarcinoma has been widely investigated in most recent years; however, there have been no effective treatment strategies. For most of the current studies concerning the etiology of lung adenocarcinoma, the A549 cell line provides an excellent model for the investigation of lung cancer and, therefore, is widely used 32, 33, 34. In this study, we demonstrated that the suppression of BCL-xL by let-7a-5p enhanced autophagy but repressed migration and invasion in A549 lung cancer cells, which was tightly associated with the activation of the PI3K-signaling pathway.…”
Section: Discussionmentioning
confidence: 65%
“…Consistently, ectopic expression of miR-24-3p suppressed the cell migration, invasion, and proliferation of MCF7, Hep3B, B16F10, SK-Hep1, and PC-3 cells by directly targeting p130Cas(42). Moreover, let-7a-5p inhibited BCL2L1 expression and suppressed lung cancer cell proliferation, migration, and invasion(43). LncRNA NEAT1 promotes colorectal cancer cell proliferation and migration via regulating glial cell-derived neurotrophic factor by sponging miR-196a-5p(44).…”
mentioning
confidence: 67%